Support effect boosting the electrocatalytic N2 reduction activity of Ni2P/N, P-codoped carbon nanosheet hybrids. Issue 5 (17th January 2020) - Yuan, Menglei; Zhang, Honghua; Gao, Denglei; He, Hongyan; Sun, Yu; Lu, Peilong; Dipazir, Sobia; Li, Qiongguang; Zhou, Le; Li, Shuwei; Liu, Zhanjun; Yang, Junhan; et al.
Abstract : A Ni2 P/N, P-codoped carbon nanosheet were prepared. The N, P-C substrate is regarded as an electronic storage medium which playing a vital role in inhibiting the adsorption of H + and promoting activation of N2 molecules. Abstract : Electrochemical reduction of N2 into NH3 (N2 RR) under ambient conditions has emerged as a sustainable approach alternative to the Haber–Bosch process. However, the more favored H + reduction in aqueous electrolytes can lead to low faradaic efficiency for NH3 production. Thus, designing electrocatalysts to suppress proton reduction is the key to improve the activities towards the N2 RR. As an efficient strategy for modulating the associated electronic properties of surface catalysts, the support effect is drawing growing attention. Sparked by the support effect, Ni2 P nanoparticles supported by N, P co-doped carbon nanosheets (Ni2 P/N, P-C) were synthesized and found to have a higher affinity for N2 molecules than for H + which makes it a good candidate for the N2 RR. The prepared catalyst showed an NH3 yield rate of 34.4 μg h −1 mgNi2P −1 at −0.2 V vs. the reversible hydrogen electrode (RHE) with a faradaic efficiency of 17.21% in 0.1 M HCl (22.89% and 57.2 μg h −1 mgNi2P −1 in 0.2 M PBS; 19.82% and 90.1 μg h −1 mgNi2P −1 in 0.1 M KOH), which is higher than the best values ever reported for noble-metal free catalysts in aqueous solution under ambient conditions. Importantly, the N, P-C substrate in this work is regarded as an electronic storage medium that regulates the electronic distribution of Ni2 P/N, P-C when N2 is chemically adsorbed at the Ni site, playing a vital role in inhibiting the adsorption of H and promoting the adsorption and activation of N2 molecules. This work not only gives a new insight into understanding the transformation of the HER to the N2 RR, but also provides a guideline for the development of highly active non-noble-metal catalysts.